Analysis of Occupational Health and Safety (OHS) Implementation Procedures in the Apron Movement Control (AMC) Unit at the Public Service Agency of Juwata Tarakan Class I Main Airport Operator - Arya Soeadyfa Fridyatama, Dimas; Pambudiyatno, Nyaris; Miranda Listiantika, Dinda (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Occupational Health and Safety (OHS) is a crucial aspect of aviation operations, particularly in apron areas that carry a high level of risk. This study aims to analyze the implementation procedures of OHS at the Apron Movement Control (AMC) Unit of Juwata Airport, Tarakan, and to evaluate their effectiveness in creating a safe working environment.This research employs a descriptive qualitative method using data collection techniques such as observation, interviews, and documentation. The findings indicate that, in general, OHS procedures have been implemented by AMC personnel; however, the implementation has not been optimal. Violations in the use of Personal Protective Equipment (PPE), limited safety facilities, and inadequate supervision of hazards such as Foreign Object Debris (FOD) were still found. Although personnel awareness and understanding of OHS are considered fairly good, they are not yet evenly distributed. Efforts to improve discipline, such as training, regular briefings, and the imposition of sanctions, have been carried out, but supervision and evaluation still need to be strengthened.This study recommends increasing the quantity and equitable distribution of PPE, continuous training programs, and strengthening a culture of safety in the workplace. With appropriate short-term and long-term strategies, the implementation of OHS in the AMC Unit is expected to become more effective and consistent.